More Secure Network Communication Design Using Donut Architecture and Blum-Goldwasser Public Encryption - Semuil Tjiharjadi (Jurusan Teknik Informatika, Fakultas Teknologi Industri, Universitas Islam Indonesia, 2006)
This paper describes how to design a system using Donut architecture, that can divide data to several parts and then send them after encrypt them using Blum-Goldwasser algorithm. Uniquely, even parts of them are lost; the system can reconstruct them and build data completely without losing any information.This system can be used to send data remotely to control sensitive machine that needs accurate data to perform its actions. Invalid data or incomplete data can cause problem, especially when the data have to be sent remotely, and there are hackers, bad connection and others communication problems. It needs extra effort to make sure accurate data and this system is one of the solutions to solve these kinds of problems.The result is a system that able to encrypt, divide, send and recover data completely if the loss factor fewer than 30%. System also can detect if there are problems of data validity.Further research is how to use this technique to divide database and then spread them to several server in spread locations and how to protect them. The system certainly has to be able to combine and recover data completely when some servers are crash and lost their data.Keywords: durable, secure, encrypt, integrity